1998
DOI: 10.1002/hrdq.3920090302
|View full text |Cite
|
Sign up to set email alerts
|

A win‐win paradigm for quality of work life and business performance

Abstract: This study develops and tests hypotheses to examine empirically how the perceived image ofa company's quality ofwork life will affect'its market and financial performances. Growth and profitability of two groups of publicly held companies were compared bused on sales growth, asset growth, return on equity, and return on assets. Thefirst group consisted ofjfty-eight companies identified as the best companies to workfor in the United States; the second group consisted of eighty-eight of Standard and Poor's top o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0
14

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(114 citation statements)
references
References 17 publications
2
89
0
14
Order By: Relevance
“…The results support the Walton (1975) about the QWL is defined as a balance between the desire and interest towards corporate social responsibility. The results of this study are also consistent with the results of research Horst et al (2014) Santercole (1993), French et al, (1990), Luthans (1995), Lau andMay (1998), Jewell andSiegall (1998) Kondalkar (2009) and Naude (2010), which states that the QWL has strong effect on employee productivity. The quality of work life related to the high level of satisfaction of individuals who are enjoying his work in the organization.…”
Section: Productivity Analysis Modelsupporting
confidence: 92%
“…The results support the Walton (1975) about the QWL is defined as a balance between the desire and interest towards corporate social responsibility. The results of this study are also consistent with the results of research Horst et al (2014) Santercole (1993), French et al, (1990), Luthans (1995), Lau andMay (1998), Jewell andSiegall (1998) Kondalkar (2009) and Naude (2010), which states that the QWL has strong effect on employee productivity. The quality of work life related to the high level of satisfaction of individuals who are enjoying his work in the organization.…”
Section: Productivity Analysis Modelsupporting
confidence: 92%
“…QWL is defined as "the interaction between work environment and personal needs (personal needs are satisfied when rewards from the organisation, such as compensation, promotion, recognition and development meet their expectations)" (Hackman and Oldham 1980); "the quality of the relationship between employees and the total working environment, with human dimensions added to the usual technical and economic considerations" (Davis 1983); "a way of thinking about people, work and organisations" (Nadler and Lawler 1983); "quality of working life was associated with satisfaction with wages, hours and working conditions, describing the "basic elements of a good quality of work life" as; safe work environment, equitable wages, equal employment Sosyoloji Araştırmaları Dergisi / Journal of Sociological Research -2014 / 2 opportunities and opportunities for advancement (Mirvis and Lawler 1984); "the workplace strategies, operations and environment that promote and maintain employee satisfaction aimed at improving working conditions for employees and organisational effectiveness" (Lau and Bruce 1998); "a generic concept that covers a person's feelings about every dimension of work, and a way of thinking about people, work and organization that involves a concern for employee well-being and organizational effectiveness" (Yousuf 1996;Cummings and Worley 1997); "employee satisfaction with a variety of needs through resources, activities, and outcomes stemming from participation in the workplace" (Sirgy et al 2001); "the favourable working environment that supports and promotes satisfaction by providing employees with rewards, job security and career growth opportunities" (Lau et al 2001).…”
Section: The Quality Of Work Life Was Put Forward As a Discipline In mentioning
confidence: 99%
“…According to Akdere (2006), the issue of work life quality has become critical in the last two decades due to increasing demands of today's business environment and family structure. May, Lau and Johnson (1999) suggested that companies offering better QWL and supportive work environments would likely gain leverage in hiring and retaining valuable people and companies with high QWL enjoy exceptional growth and profitability (Lau & May, 1998). In the beginning, QWL is synonymous with employability rate, job security, earnings and benefits (Elizur & Shye, 1990).…”
Section: Introductionmentioning
confidence: 99%